2016
DOI: 10.1097/mlr.0000000000000532
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes are Worse in US Patients Undergoing Surgery on Weekends Compared With Weekdays

Abstract: Patients undergoing nonemergent major cardiac and noncardiac surgery on the weekends have a clinically significantly increased risk of death and major complications compared with patients undergoing surgery on weekdays. These findings should prompt decision makers to seek to better understand factors, such physician and nurse staffing, which may contribute to the weekend effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 24 publications
3
80
4
1
Order By: Relevance
“…Acute conditions requiring time critical diagnosis or intervention may be hampered by deficient resources and staffing at weekends 18, 33 . Generic studies may not account for the heterogeneity of emergency provisions across specialities and may explain the equipoise in evidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute conditions requiring time critical diagnosis or intervention may be hampered by deficient resources and staffing at weekends 18, 33 . Generic studies may not account for the heterogeneity of emergency provisions across specialities and may explain the equipoise in evidence.…”
Section: Discussionmentioning
confidence: 99%
“…The policies have imparted an ethos of multi-disciplinary care, early surgery and targeted rehabilitation, with a notable reduction in TDM 14 . However, we do not know whether the day of admission influences patient outcomes and overall survival 18, 19 .…”
Section: Introductionmentioning
confidence: 99%
“…A number of relatively small studies, generally of patients having scheduled surgery, have reported inconsistent and inconclusive variation in postoperative mortality between weekdays and the weekend . Similarly, a number of studies have reported inconsistent associations of postoperative mortality with the time of day surgery was started .…”
Section: Introductionmentioning
confidence: 99%
“…First, as compared with weekday teams (of surgeons, anesthesiologists, and nurses), weekend call teams may have less expertize to care for specific surgical problems. 13 On weekends, on-call anesthesiologists and surgeons may respond to surgical procedures not typically covered on weekdays. 13 Second, in comparison with weekdays, attending anesthesiologists may cover more cases and supervise more extenders (nurse anesthetists or residents) on weekends, especially when patients requiring emergency surgery are added to the schedule.…”
Section: Discussionmentioning
confidence: 99%
“…In total, of these three studies, 9,13,14 endovascular aortic repair in the weekend group (18.2%) was performed significantly (p < 0.00001 by χ 2 tests) less than that in the weekday group (30.8%). Although endovascular aortic repair was adjusted for using multivariable analyses in only one 14 of these studies, 9,13,14 the impact of endovascular aortic repair on early mortality was not reported.…”
Section: Sensitivity Analysesmentioning
confidence: 99%